Chapter 4: Sustainability transitions by ecosystem innovation - Wolff, Joel (Edward Elgar Publishing, 2023)
The aim of this chapter is to explore the role of ecosystems in sustainability transitions. The chapter begins by identifying global challenges in relation to business and management and comparing the emerging conceptual landscape of sustainability governance and corporate social responsibility. Then, it explores sustainability transitions as a system-level phenomenon and discusses the opportunities that ecosystems open for innovation in this context. The findings suggest that ecosystems open new insight into the present discussion on sustainability transitions. By enabling novel forms of collaboration and governance, ecosystems allow solution-specific innovation, development, and realisation of innovative value propositions influencing the wider industry and society. Furthermore, this chapter argues that ecosystems can support more sustainable forms of production, knowledge creation, and business activities. This chapter contributes to both management and sustainability transitions theory by showing how the current discourses on sustainability governance and corporate social responsibility call for novel forms of governance, collaboration, and co-creation of knowledge across geographical and socio-economic boundaries. The conclusion is that ecosystems offer a promising construct for inducing the collaboration among diverse agents to enable innovation for mitigating global challenges. Lastly, this chapter suggests that to validate these claims, further research is needed to establish how ecosystems may be governed and evolve over time.